2022
DOI: 10.3174/ajnr.a7401
|View full text |Cite
|
Sign up to set email alerts
|

Impact Analysis of Different CT Configurations of Carotid Artery Plaque Calcifications on Cerebrovascular Events

Abstract: BACKGROUND AND PURPOSE: CT is considered the standard reference both for quantification and characterization of carotid artery calcifications. Our aim was to investigate the relationship among different types of calcium configurations detected with CT within the plaque with a novel classification and to investigate the prevalence of cerebrovascular events. MATERIALS AND METHODS:Seven hundred ninety patients (men = 332; mean age, 69.7 [SD,13] years; 508 symptomatic for cerebrovascular symptoms and 282 asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“… 37 , 38 On the other hand, other calcium configurations such as intimal or superficial calcifications, or type 3, deep, or bulky calcifications, are rarely associated with the occurrence of cerebrovascular events. 39 …”
Section: Supracardiac Atherosclerosismentioning
confidence: 99%
“… 37 , 38 On the other hand, other calcium configurations such as intimal or superficial calcifications, or type 3, deep, or bulky calcifications, are rarely associated with the occurrence of cerebrovascular events. 39 …”
Section: Supracardiac Atherosclerosismentioning
confidence: 99%
“…Among the multiple parameters that have been indicated as responsible for an increased vulnerability, conflicting results have emerged in the identification of a role for calcium. Emerging research has suggested various mechanisms in calcium deposition leading to different phenotypes of carotid plaque calcification [97][98][99][100][101]. Yang et al investigated the association between calcium configurations and ulceration with IPH, demonstrating that superficial, multiple, and thin calcifications were associated with IPH.…”
Section: Features Of Vulnerabilitymentioning
confidence: 99%
“…Recent reports showed that rim sign (plaque adventitial calcification) or ulceration on computed tomography angiography (CTA) is correlated with intraplaque hemorrhage (IPH) or symptomatic carotid artery stenosis. 1,[4][5][6] We aim to investigate the association of recurrent ischemic events in symptomatic mild to moderate carotid stenosis with specific plaque findings on CTA.…”
mentioning
confidence: 99%
“…The interactive window/level setting was usually set at W850.L300. 6 The images were evaluated by two blinded neurosurgeons (TT and KY). CTA markers included the degree of stenosis (NASCET criteria) and presence of rim sign, ulceration, and intraluminal thrombus.…”
mentioning
confidence: 99%
See 1 more Smart Citation